THE DIFFERENCE ANALYSIS OF ABNORMAL RETURN AND TRADE VOLUME ACTIVITY BEFORE AND AFTER RAMADHAN EFFECTS ON FOOD AND BEVERAGES COMPANIES LISTED IN INDONESIAN SHARIA STOCK INDEX (ISSI) - TITIN HARTINI; AMRI AMIR; JUNAIDI JUNAIDI; TONA AURORA LUBIS (Journal of Business Studies and Management Review, 2019)
This study aims to determine the difference between abnormal return and trade volume activity before and after Effects on Food And Beverages Companies Listed in Indonesian Sharia Stock Index (ISSI) in 2012 until 2017. In this study, samples were taken as many as 7 companies in the food and beverages sector. Researchers use quantitative research methods. The sampling technique used is purposive sampling. The type of data used is secondary data. Data analysis techniques are use parametric paired sample t-test and non parametric wilcoxon sign rank test using IBM SPSS 23 program.The results showed that there were significant differences of abnormal return between the month of sha'ban and syawal with significance value 0.003 < 0 .05. However there is a significant difference in trade volume activity between the month of sha'ban and the month of syawal with a significance value of 0.003 < 0.05. it can be concluded that Ramadhan has information on the market that causes abnormal return and changes in trade volume activity.